(untitled) (Nordic Journal of African Studies, 2004)
Spirit possession phenomena spread to the Maasai area in Northern Tanzania especially in the 1960s and 1970s. Among the Maasai, spirit possession was not part of established cultural behaviour, although possession phenomena and associated healing cults were common among the surrounding ethnic groups of Bantu origin. The phenomenon received epidemiological proportions, and in some areas about half of adult female population claimed to have experienced spirit possession. In the 1980s the phenomenon started to diminish and has continued to do so in recent years. The traditional healers of the coastal area had a role to play in treating the affected people, but at the same time they contributed to the spreading of the phenomenon. The role of the Christian Churches was instrumental in coping with the phenomenon, and it has practically disappeared in the areas where the role of the Church has been significant. Spirit possession, which affected almost exclusively women, can be seen as a major channel for change in a male-dominated society. The study is based primarily on 91 possession cases. Information was collected during several fieldwork periods between the years 1970 and 1996.